EVALUASI BIAYA OPERASI DAN PENYUSUTAN PENDAPATAN PADA PT PLN (PERSERO) WILAYAH PAPUA - mugiati, Mugiati; Aditama, Muhammad Irfan (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2025)
This study aims to determine the effect of operating costs and depreciation on the income of PT. PLN (Persero) in the Papua region. The analytical tool used in this study is multiple regression to determine the effect of the independent variable (X) on the dependent variable (Y). The results of the study prove that there is a positive and significant effect of operating costs on income. This can be seen from the value of ttable> tcount (3.018> 2.015) with a significance of 0.048 <0.05. The results of this study indicate a significant relationship between operating costs and income. This means that the higher the operating costs incurred by PT. PLN Persero in the Papua region will increase income, conversely the lower the operating costs incurred will decrease income at PT. PLN Persero Jayapyra Branch. Losses between have a positive and significant effect on income depreciation. This can be seen from ttable> tcount (4.807> 2.015) with a significance of 0.041 <0.05. The results of this study indicate a significant relationship between depreciation and income. This means that the higher the loss felt by PT. PLN Persero Papua region, the lower the income will be, conversely, the lower the depreciation owned by PT. PLN Persero Papua region, the higher the income will be.